Opportunities and challenges of transfer reactions at HIRFL-CSRe - Wan 万, W. W. 文武; Liang 梁, S. Q. 诗琪; Lou 楼, J. L. 建玲; Pang 庞, D. Y. 丹阳; Tu 涂, X. L. 小林; Zhang 张, Y. H. 玉虎; de Angelis, G.; Kaminski, G.; Li 李, Q. T. 奇特; Ge 葛, H. Y. 浩煜; Zhu 朱, H. Y. 宏渝; Xia 夏, B. L. 博龙 (Chinese physics C, 2025)
The opportunities and challenges of performing transfer reactions in inverse kinematics using the 16,18 O beams at the experimental Cooler Storage Ring (CSRe) of the Heavy Ion Research Facility in Lanzhou (HIRFL) with the internal gas-jet target are discussed herein. The kinematics, differential cross sections for various transfer reactions using the 16,18 O beam with incident energies of 30 and 100 MeV/nucleon, and the H 2 - or D 2 -gas-jet targets are compared. The 16 O beam at 100 MeV/nucleon with an intensity of ≥10 6 pps interacting with the H 2 -gas-jet target is recommended as the first transfer reaction at HIRFL-CSRe.